In situ reduction of silver nanoparticles by chitosan-l-glutamic acid/hyaluronic acid: Enhancing antimicrobial and wound-healing activity. (1st October 2017) - Lu, Bitao; Lu, Fei; Zou, Yini; Liu, Jiawei; Rong, Bao; Li, Zhiquan; Dai, Fangying; Wu, Dayang; Lan, Guangqian
Graphical abstract: Highlights: AgNPs loaded Chitosan-l -glutamic acid/hyaluronic acid sponge dressings were successfully prepared by an in-situ reduction. The dressing showed good antibacterial efficacy and cytotoxicity. The increas of AgNP content improved antibacterial property and mechanical properties of the sponge dressings. The dressings prove effective for accelerating the healing rate of cutaneous wounds in rabbits. Abstract: Spongy composites with silver nanoparticles (AgNPs) were synthesized by freeze-drying a mixture of silver nitrate (AgNO3 ) and chitosan-l -glutamic acid (CG) derivative loaded with hyaluronic acid (HA) solution. CG/AgNP spongy composites had an interconnected porous structure and rough surfaces. When AgNPs (5–20 nm) were immobilized on these spongy composites, AgNP aggregation was dependent on AgNO3 concentration. The spongy composites exhibited good mechanical properties, swelling, and water retention capacity. In vitro antibacterial activity showed that the CG/AgNP spongy composites effectively inhibited bacterial ( Escherichia coli and Staphylococcus aureus ) growth and penetration. Spongy composites containing low concentrations of AgNP were non-toxic to L929 cells, while CG/HA/AgNP spongy composites promoted wound healing, as determined by in vivo tests, wound contraction ratio, average healing time, and histological examination. These results indicate that the spongy composites can serve as effective antibacterial wound dressings.